PENGARUH KUALITAS PELAYANAN, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PENGGUNAAN TRANSPORTASI ONLINE GRABCAR - Teuku Ilyas Rinaldi, (2020)
In the era of globalization as it is today, in Indonesia. Public transportation companies in the global economy are increasingly advancing rapidly encouraging companies to improve consumer use decisions so they continue to be interested in the services offered. Then arose various transportation service companies to increase company sales by taking into account technological factors that could increase profits doubled in the future for example Grabcar. So this research was made to find out whether the decision to use Grabcar online transportation is influenced by the decision to use, price, and promotion. This research is a quantitative study and the population is the people who have used Grabcar services. Samples taken were 75 respondents using probability sampling and purposive sampling methods. Data collection using a questionnaire distributed to the respondents. The analysis technique used is Partial Least Square (PLS) with SmartPLS 3.0 software. The results obtained from this study explain that the quality of service significantly influences the decision to use Grabcar online transportation, while the price and promotion does not significantly influence the decision to use Grabcar online transportation.